2021
DOI: 10.1098/rspb.2020.2898
|View full text |Cite
|
Sign up to set email alerts
|

Weapon performance drives weapon evolution

Abstract: Many sexually selected traits function as weapons, and these weapons can be incredibly diverse. However, the factors underlying weapon diversity among species remain poorly understood, and a fundamental hypothesis to explain this diversity remains untested. Although weapons can serve multiple functions, an undeniably important function is their role in fights. Thus, a crucial hypothesis is that weapon diversification is driven by the evolution of weapon modifications that provide an advantage in combat (e.g. c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…It is somewhat surprising to find that weapon performance has a lower influence on contest success when compared to weapon size, especially given previous evidence that weapon performance has a substantial influence on contest success [and on weapon evolution (e.g. Lappin & Husak, 2005; Palaoro et al ., 2020; Emberts, Hwang & Wiens, 2021)]. However, interpreting these results requires caution because of the biases and limitations within the available literature.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is somewhat surprising to find that weapon performance has a lower influence on contest success when compared to weapon size, especially given previous evidence that weapon performance has a substantial influence on contest success [and on weapon evolution (e.g. Lappin & Husak, 2005; Palaoro et al ., 2020; Emberts, Hwang & Wiens, 2021)]. However, interpreting these results requires caution because of the biases and limitations within the available literature.…”
Section: Discussionmentioning
confidence: 94%
“…Other species are known to use piercing weapons [e.g. hummingbirds (Rico‐Guevara & Araya‐Salas, 2015) and coreid bugs (Emberts et al ., 2021)] but they were not included in our meta‐analysis because they did not meet our inclusion criteria (e.g. did not involve contests or did not have suitable data).…”
Section: Discussionmentioning
confidence: 99%
“…What is even less clear is why selection would favour investment into divergent head shapes and how this might relate to a species ecology (i.e. the divergent context hypothesis; Emberts et al., 2021; Emlen, 2008). Most brentines are associated with dead wood, either as deadwood feeders (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, in some Hemiptera species of the Coreidae family, agonistic interactions involve using spines on the hind legs to damage the rival's wings (Emberts & Wiens, 2021). In these species, both the femur size and the hind legs morphology are important in explaining the extent of the damage caused (Emberts et al, 2021). In fact, a recent review found that weapon size seems to be less important in determining the winner in agonistic interactions in which the weapon is primarily used to cause damage than in interactions in which the weapon is primarily used to push or pull the rival (Palaoro & Peixoto, 2022).…”
Section: Discussionmentioning
confidence: 99%